A new construction approach for tiny house on wheels: POD THOWs - Tayfur Emre Yavru; Gürkan Topaloğlu; Güray Yusuf Baş; Semih Yılmaz (Vitruvio: International Journal of Architectural Technology and Sustainability, 2023)
Although the size of the houses has increased in recent years, the number of house users is decreasing. The decrease in the number of users has brought forth the concept of tiny houses which use less materials, less energy, and produce less waste compared to large houses. There are several types of tiny houses, with tiny houses on wheels (THOWs) being the most preferred type. However, THOWs are subject to high-way rules because they are not permanent structures. Such rules limit the dimensions of THOWs, thus preventing the creation of necessary spaces in the interior. In this study, we exanimated mobile housing, revealed barriers to their use and dissemination, and proposed a system called POD-THOW, which could offer a solution to the space needs of THOWs. As a result, it was understood that POD-THOWs provide a solution to size restrictions, but they should be combined with lightweight constructions and sustainable energy sources to prove effective.